The Multiple Affinities of α-Dystroglycan - Sciandra, Francesca; Bozzi, Manuela; Giulia Bigotti, Maria; Brancaccio, Andrea (Current Protein and Peptide Science, 2013)
The dystroglycan (DG) adhesion complex is formed by the peripheral α-DG and the transmembrane β-DG, both originating from the same precursor. α-DG plays a crucial role for tissue stability since it binds with high affinity a variety of proteins and proteoglycans in many different cell types. One common molecular feature of most of the α-DG ligands is the presence of laminin globular (LG) domains that are likely to interact with some of the carbohydrates protruding from the mucin-like region of α-DG. Every tissue is supposed to produce a specific α-DG harboring a particular sugar moiety that will enable it to bind a specific ligand, but often several α-DG ligands are co-expressed within the same tissue. It is therefore very important to assess all these different interactions, ultimately measuring the affinity constants (KDS) underlying them. Herein, we present an updated list of α-DG interactors, including non LG-domains containing ligands, offering both a historic perspective on the original contributions made by several laboratories and an update on the different techniques used and the KD values obtained so far. For the cure of some muscular dystrophies, the reinstatement of a prominent affinity between α-DG and one of its vicarious ligands is becoming an increasingly popular choice for strengthening the basement membrane-tissue connection. An update on the current available information about α- DG′s multiple, and often “concomitant“ affinities, may be of interest for those wishing to better direct their molecular therapy approaches. A final paragraph is dedicated to comment on the evidence that an increase in affinity is not always advantageous.
Keywords: binding affinity constants